2003
DOI: 10.1021/la026983q
|View full text |Cite
|
Sign up to set email alerts
|

Electroacoustic Study of the Crystallization of n-Eicosane Oil-in-Water Emulsions

Abstract: When sodium dodecyl sulfate-stabilized emulsions of n-eicosane are supercooled from about 40°C, solidification of the droplets occurs below 24°C; reheating the suspension causes the particles to melt at the normal melting point of 36-37°C, and the emulsion returns to its initial state without any aggregation or coalescence observed. The crystallization changes the density of the particles and the volume fraction of the suspension. When this is properly considered, the dynamic mobility spectra obtained from ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Recent work by Nespolo et al 1 has shown that for surfactant stabilised decane emulsions the liquid-liquid interface does behave like a solid-liquid interface. Similarly, we have shown 2 that there is no significant change in the electrokinetic properties of eicosane emulsions whether they are liquid or solid, implying that there is no momentum transfer across the interface.…”
Section: Introductionsupporting
confidence: 57%
“…Recent work by Nespolo et al 1 has shown that for surfactant stabilised decane emulsions the liquid-liquid interface does behave like a solid-liquid interface. Similarly, we have shown 2 that there is no significant change in the electrokinetic properties of eicosane emulsions whether they are liquid or solid, implying that there is no momentum transfer across the interface.…”
Section: Introductionsupporting
confidence: 57%
“…EA spectroscopy can also be used to provide information about the droplet size distribution of emulsions; however, the droplet size range is usually rather limited (∼0.1−10 μm). The major advantage of the EA technique over more conventional microelectrophoretic (ME) techniques based on light scattering is that it is capable of analyzing emulsions with high droplet concentrations (<50%) without any sample dilution. ,, EA techniques have been used to measure particle size distributions and ζ-potentials in a wide variety of different model and industrial oil-in-water (O/W) and water-in-oil (W/O) emulsions. ,, Nevertheless, there are some limitations of the EA technique for certain applications. For example, the droplets must have an electrical charge, there must be a significant density contrast (Δρ > 2%) between the droplets and the surrounding liquid, and the viscosity of the continuous phase must be known at the measurement frequency (which is not always the same as that measured in a conventional viscometer).…”
Section: Introductionmentioning
confidence: 99%